Prevention of Hepatitis B Virus Transmission in Pregnancy - Dwi Rahayu NL Praptiwi; Andri Sanityoso (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Chronic hepatitis B virus infection is a serious health problem in many countries, particularly in developing countries. In Asia-Pacific region, vertical transmission from mother to child is the main endemicity factor of hepatitis B virus (HBV) infection. Almost 50% cases of hepatitis B virus infection happen during perinatal and neonatal period, including vertical transmission from mother to child during pregnancy.World Health Organization (WHO), World Gastroenterology Organization (WGO) and many countries have recommended immunoprophylaxis by the administration of hepatitis B vaccine and hepatitis B immunoglobulin (HBIg) to prevent transmission from mother to child. However, there are approximately 10-15% babies born from mother with hepatitis B infected by HBV through intrauterine transmission. Incidence of intrauterine transmission is accounted for around 43-50% if DNA of HBV in the mother is more than 107 copies/mL, although passive and active immunization to the baby has been administered. Therefore, administering antiviral drugs in pregnant women with chronic hepatitis B accompanied by immunoprophylaxis is effective in preventing hepatitis B infection transmission during pregnancy, particularly in decreasing the number of virus and administering active or even passive immunization to neonates. Keywords: hepatitis B, pregnancy, prevention, transmission